Implementación del diseño de la automatización de la ralladora de yuca para la producción de concentrados porcinos en la Universidad Antonio Nariño Sede Cartagena (2021)
The objective of this project is to implement the design of an automated cassava grating machine for agribusiness, at the Antonio Nariño University in Cartagena, by installing the components of the design previously proposed by students from the same institution in the second semester of the year 2019. In the same way, it is proposed to find opportunities for improvement, and with the functional tests with raw material, to carry out a cost / benefit analysis of the machine under study, which is located at the Antonio Nariño University in Cartagena. The scope of this project is given from what is established in the proposed design (automated, production capacity, etc.) To the cost / benefit analysis as part of the studies carried out by an educational institution and limited in time for its execution.